2020
DOI: 10.4054/demres.2020.42.31
|View full text |Cite
|
Sign up to set email alerts
|

Fertility patterns of migrants from low-fertility countries in Norway

Abstract: BACKGROUND Most research on migrant fertility focuses on immigrants from high-fertility countries who have moved to countries with lower fertility. Little is known about the fertility of immigrant women from countries where fertility is lower than in the destination country. OBJECTIVE This study investigates fertility rates among women from low-fertility countries who have moved to a country where fertility is comparatively higher (Norway). METHODS Register data on immigrant women from Poland, Lithuania, and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…There is some evi dence that the fer til ity lev els of "lowfer til ity" immi grants (mea sured in dif fer ent ways) are higher for those who have a lon ger dura tion of res i dence than for those who recently arrived. For exam ple, this appears to be the case for Roma nians in Italy (Mussino and Strozza 2012), Ger man immi grants in Norway (Tønnesen and Mussino 2020), and immi grants from the Soviet Union in Israel (Nahmias 2004), although the lat ter is some what contradicted in another study of Israel (Okun and Kagya 2012). It is tempt ing to inter pret these find ings as evi dence for or against adap ta tion, but they are poten tially con founded by the forces of antic i pa tion, dis rup tion, and selec tion, because they focus on immi grants who arrived as adults.…”
Section: Old Theories For a New Approachmentioning
confidence: 95%
See 1 more Smart Citation
“…There is some evi dence that the fer til ity lev els of "lowfer til ity" immi grants (mea sured in dif fer ent ways) are higher for those who have a lon ger dura tion of res i dence than for those who recently arrived. For exam ple, this appears to be the case for Roma nians in Italy (Mussino and Strozza 2012), Ger man immi grants in Norway (Tønnesen and Mussino 2020), and immi grants from the Soviet Union in Israel (Nahmias 2004), although the lat ter is some what contradicted in another study of Israel (Okun and Kagya 2012). It is tempt ing to inter pret these find ings as evi dence for or against adap ta tion, but they are poten tially con founded by the forces of antic i pa tion, dis rup tion, and selec tion, because they focus on immi grants who arrived as adults.…”
Section: Old Theories For a New Approachmentioning
confidence: 95%
“…Consequently, there is a lack of research on immi grants who were born in countries with belowreplace ment fer til ity, that is, from low-fer til ity ori gins. This is unfor tu nate because stud ies of immi grants from lowfer til ity ori gins have a sim i lar or per haps even greater poten tial for test ing the o ries of fer til ity adap ta tion (Tønnesen and Mussino 2020). At pres ent, there is lit tle evi dence whether fer til ity adap ta tion occurs among immi grants from lowfer til ity set tings, despite the prom i nence of migra tion streams from lowfer til ity ori gins in many des ti na tions (Castles et al 2013;Livi Bacci 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has the potential to provide information on processes of social integration, as migrants' childbearing behaviour is prone to change over time as their locations and life situations change. Clearly, it is equally instructive to study migrants who move from a high-to a low-fertility setting (e.g., Milewski 2007;Dubuc 2012) as it is to study those who move from a low-to a less low-fertility context (e.g., Hwang and Saenz 1997;Okun and Kagya 2012;Tønnessen and Mussino 2020;Mussino et al 2020). The study of migrants from low-fertility settings has the potential to reveal some of the reasons for the unrealised fertility intentions (Beaujouan and Berghammer 2019) in the migrants' countries of origin; and, perhaps, to shed light on the logics of the low and lowest-low fertility levels of many regions in Europe.…”
Section: Migration and Fertilitymentioning
confidence: 99%
“…The current study examines the quantum of childbearing of migrants from low-fertility contexts (Poland and Romania) at multiple destinations (Italy and the United Kingdom), and compares them to stayers at origin and to non-migrants at destination. Few studies have focused on the fertility of migrants from low-fertility countries, although these groups are less likely to have children prior to or around the time of migration (Tønnessen and Mussino, 2020) and have consequently been claimed to facilitate the testing of the adaptation 'from below' at net of the impact of interrelated demographic events. While most of the existing studies have found some evidence of adaptation among specific groups -e.g.…”
Section: Introductionmentioning
confidence: 99%
“…While most of the existing studies have found some evidence of adaptation among specific groups -e.g. Germans in Norway (Tønnessen and Mussino, 2020), migrants from the Soviet Union in Israel (Nahmias, 2004), Chinese in the US (Hwang and Saenz, 1997), and Polish in Britain (Lübke, 2015) -others contradict or do not fully support this hypothesis (e.g. Okun and Kagya, 2012).…”
Section: Introductionmentioning
confidence: 99%